Faktor-Faktor Yang Mempengaruhi Aktivitas Tambang Galian C di Kelurahan Roworena Barat Kabupaten Ende - Fulgensia Klarista Riti; Henda Viktor Risano Taopan; Sunimbar Sunimbar (Geosfera: Jurnal Penelitian Geografi, 2025)
Mining of pebbles and sand occurs because the mining community does not have agricultural land. Mining activities carried out can provide employment and as a source of income. But on the other hand, this activity has the potential to have a direct impact on the environment such as landslides and road damage, which occurred in West Roworena Village. This study aims to determine the influence of infrastructure, institutions, and the environment on mining activities in West Roworena Village, North Ende District, Ende Regency.and to determine the management strategy of the C excavation mine in West Roworena Village, North Ende District, Ende Regency. This study is a descriptive analysis with a mixed approach (mix methoed). Data was collected through observation, questionnaires, interviews, and documentation. The analysis used in this study is multiple regression analysis and SWOT analysis. The results of the study showed that (1) Infrastructure, institutional, and environmental variables had a positive effect on mining activities with a value of 67.3%. (2) the management strategy of the C mine based on the results of the analysis of the strategy that uses the strengths and opportunities in quadrant I, which is in the form of the strategy of "management of the C mining by utilizing local technology and resources in improving the community's economy".